Optimising endocrine therapy in postmenopausal women with advanced breast cancer - Yau, Thomas Ho Lai; Cheung, Kwok-Leung (Bioscientifica, 2018)
Hormone receptor-positive breast cancer is commonly treated with endocrine therapy; however, overtime cancer cells can develop endocrine resistance. This review aims to document combination therapy and sequential therapy in the use of endocrine agents and targeted agents. By conducting two systematic searches using 4 databases: Cochrane Library, MEDLINE, EMBASE, and Web of Science. A total of 26 studies that covered combination therapy were obtained and included for the review. 14 were phase III documenting combinations of mechanistic target of rapamycin (mTOR), phosphoinositide-3-kinase (PI3K), vascular endothelial growth factor receptor (VEGFR), human epidermal growth factor receptor 2 (HER2), and cyclin dependent kinase 4/6 (CDK4/6) inhibitors. The remaining studies were of phase II nature that reported combinations involving inhibitors in mTOR, endothelial growth factor receptor (EGFR), CDK4/6, and tyrosine kinase inhibitor (TKI). Interesting findings in inhibitor combinations involving; CDK4/6, mTOR and PI3K suggest clinical activity that can overcome endocrine resistance. On the other hand, there were 0 studies that covered sequential therapy. Overall findings showed that combination therapy improved treatment efficacy over monotherapy in postmenopausal patients with hormone-receptor positive advanced breast cancer. Inevitably, the benefits are accompanied with increased toxicity. To optimise endocrine therapy, further research into combinations and effective patient selection will need to be defined. Additionally, this review warrants future studies to explore sequential therapy.